Constraints based scheduling in the multi-project environment - Skołud, Bożena; Zientek, Aleksandra (Computer Assisted Methods in Engineering and Science; Vol 12 No 2-3 (2005), 2022)
The paper deals with the problem of new projects acceptance into the multi project environment, where constraints are limiting the number of projects that a company is able to carry out concurrently. The objective of this paper is to answer the question: Is it possible to execute new project on time in the multiproject environment? For answering the question combination of Theory of Constraints and conditions guaranteeing project due dates with constraint-based scheduling are proposed. As a result the decision of the project implementation and the schedule of project activities, which the company is able to implement concurrently are obtained.